DESIGNING AND BUILDING EXERCISE MODEL OF TECHNICAL ENGLISH VOCABULARIES USING CALL (COMPUTER ASSISTED LANGUAGE LEARNING) - Widiawati, Yogi (Lingual Journal of Language and Culture; Vol 4 No 2 (2017)DO - 10.24843/LJLC.2017.v04.i02.p01, 2017)
The research is aimed to assist and facilitate the students of Electrical and Electronics Department of Politeknik Negeri Jakarta (State Polytechnics of Jakarta), Indonesia, in learning technical English vocabulary. As technical students, they study ESP (English for Specific Purposes) and they find some obstacles in memorizing technical vocabularies which are very important in order to read and understand manual books for laboratory and workshop. Some English technical vocabularies among others are “generate”, “pile”, “bench”, et cetera. The research outcome is software which will be beneficial for technical students, especially electrical and electronics students. This software can be used to practice their vocabulary skills, so they will be more skillful and knowledgeable. This software is designed by using the program of Rapid E-Learning Suite Version 5.2 and Flash CS3. The software practice contains some exercises on reading text and reading comprehension questions and presented with the multiple answers. This software is handy and flexible because students can bring it anywhere and be studied anytime. It is handy because this software is put and saved in CD (compact disc), so the students can take it with them anywhere and anytime they want to learn. In other words, they have flexibility to learn and practice English Technical Vocabularies. As a result, the students are found one of the ways to overcome their problems of memorizing vocabularies. The product is a kind of software which is easily used and portable so that the students can use the software anywhere and anytime. It consists of 3 (three) sections of exercises. At the end of each exercise, the students are evaluated automatically by looking at the scoring system. These will encourage them to get good score by repeating it again and again. So the technical words are not problem for them. Furthermore, the students can practice technical English vocabulary both at home and in the language laboratory by using this software. Keywords: ESP, English Technical Vocabulary, Software, portable